Structural and Mechanistic Insights into the Metalation of Fluoroarenes Mediated by a Superbasic Co(II) Bis(amide) Complex - Na Jin; Eva Hevia (CHIMIA)
Over the past decades, s-block metal amides including LiTMP and TMPMgCl.LiCl (TMP = 2,2,6,6-tetramethylpiperidide) have found widespread applications in the deprotonative metalation of aromatic compounds. In contrast, transition metal amides usually exhibit diminished basicity to metalate these substrates. Here we present an overview of the synthesis of a highly reactive TMP-based cobalt(II) bis(amide) complex Co(TMP)2 and its relevance in the direct Co–H exchange processes with fluoroarenes. This deprotonative metalation reactivity can be further extended to cyclopentadiene to generate cobaltocene. Exhibiting an unusual reactivity, Co(TMP)2 has also been found to be highly nucleophilic, as evidenced by the insertion of CO2 molecules into both of its Co–NTMP bonds.